Bankers’ perception of Green Banking: learning from the experience of Islamic banks in Bangladesh - Mohammad Masukujjaman,; Chamhuri Siwar,; Mahmud, Md. Reaz; Syed Shah Alam, (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
Malaysia once replicated Bangladesh’s trail-blazer Grameen Bank to establish its Amanah Ikhtiar model of Islamic banking for the poor. Now, it may also learn some useful things from Bangladesh’s Islamic Green Banking. In this light, this study analysed the bankers’ perceptions of the green banking concept, its benefits, its complexities of execution, and its possible relationship with Islamic banking. This is an empirical study of 48 Islamic bankers from 21 branches of seven Islamic banks located in Dhaka, Bangladesh employing structured questionnaires. Data purification and analysis were carried out through a software SPSS version 1; and Henry Garrett’s ranking technique was used to gauge the most influential factors. The analysis revealed that respective bankers perceived green banking as an environmental banking that helped to protect the environment despite its high adoption cost. Also, green banking and Islamic banking were perceived to be compatible and interlinked as Islam supports resource savings, cleanliness, ethics and social responsibility all of which are also the mottos of Green Banking.